Analysis of pharmaceutical inventory management based on ABC-VEN analysis in Rwanda: a case study of Nyamagabe district - Ephrem Mfizi; François Niragire; Thomas Bizimana; Marie Françoise Mukanyangezi (Taylor & Francis Group, 2023)
Abstract Background Pharmaceuticals account for a large portion of healthcare spending in healthcare organizations. Their effective inventory management is required to match the cost of stocks with the customer demand and avoid shortage of supplies at any health facility level. This study aimed to analyze pharmaceuticals' inventory management using ABC-VEN analysis. Methods The study was conducted at Rwanda Medical Supply (RMS) Ltd, Nyamagabe Branch for products distributed to health facilities in Nyamagabe District catchment area from the financial years 2017-2018 to 2019-2020. It consisted of a descriptive retrospective study of 457 items. The latter are generic essential medicines distributed to public health facilities during the study period. Products were arranged according to a descending order of importance, and we performed a breakdown of products according to the Pareto Principle. Following an ABC analysis of distribution data for such drugs billed to healthcare facilities, a VEN analysis was performed to identify high-value vital products that require more attention. Results During the ABC analysis, 76 products were classified in group A. These accounted for 19.84% and had a value of 74.91% of the total cost of all products. Group B included 116 products, representing 30.29% with a value of 20% of the total cost, while Group C had 191 products, representing 49.87% with a value of only 5.09% of the total cost. During the VEN analysis, 202 products (44.20%) were classified as vital, 231 (50.54%) as essential, and 24 products (75.26%) as non-vital. The analysis with ABC-VEN resulted in Class I representing 55.80% of all medicines that cost 87.88% of all total cost, Class II representing 40.70% with a total cost of 11.82%, and Class III representing 3.50% with a cost of 0.3%. Conclusions This study results show that inventory management of vital and expensive products, such as antibiotics, antihypertensive pharmaceuticals, consumables, and massive solutions would be carefully monitored to prevent a shortage of such products at health facility levels. The ABC-VEN analysis is one of the practical and affordable method to achieve their optimized supply chain.